The topology of african exports : emerging patterns on spanning trees - Araújo, Tanya (2016)
This paper is a contribution to interweaving two lines of research that have progressed in separate ways: network analyses of international trade and the literature on African trade and development. Gathering empirical data on African countries has important limitations and so does the space occupied by African countries in the analyses of trade networks. Here, these limitations are dealt with by the definition of two independent bipartite networks: a destination share network and a commodity share network. These networks - together with their corresponding minimal span- ning trees - allow to uncover some ordering emerging from African exports in the broader context of international trade. The emerging patterns help to understand important characteristics of African exports and its binding relations to other economic, geographic and organizational concerns as the recent literature on African trade, development and growth has shown.